FLIPPED CLASSROOM IN MATHEMATICS EDUCATION AFTER PANDEMIC: A SYSTEMATIC LITERATURE REVIEW - Putri, Finola Marta; Juandi, Dadang; Kusumah, Yaya Sukjaya; Martadiputra, Bambang Avip Priatna; Kusnandi, Kusnandi (ALGORITMA: Journal of Mathematics Education, 2025)
AbstractThe COVID-19 pandemic has highlighted the need for adaptive learning models, especially in mathematics education. This study aims to analyze publications on the Flipped Classroom model in post-pandemic mathematics education (2021–May 2023) and to explore its future development.  The method used is a systematic literature review of 10 articles, consisting of two Scopus-indexed articles and eight articles from Google Scholar obtained using the Publish or Perish application. The total number of participants involved in the reviewed studies is 1,200, comprising 370 elementary school students, 208 junior high school students, 179 senior high school students, and 417 university students. The findings indicate that the digital-based Flipped Classroom model can enhance mathematical communication skills, critical thinking, conceptual understanding, problem-solving abilities, and higher-order thinking. Moreover, it positively influences students' self-confidence, creates a more interactive classroom environment, generates positive learning responses, and supports social interaction in online settings. These results suggest that the Flipped Classroom is an effective instructional model and is recommended for mathematics learning in the post-pandemic era. AbstrakPandemi COVID-19 mendorong perlunya model pembelajaran yang adaptif, termasuk dalam pendidikan matematika. Penelitian ini bertujuan menganalisis publikasi mengenai model Flipped Classroom dalam pendidikan matematika pascapandemi (2021–Mei 2023) dan menggambarkan arah perkembangannya. Metode yang digunakan adalah systematic literature review terhadap 10 artikel, terdiri dari dua artikel terindeks Scopus dan delapan artikel dari Google Scholar yang diperoleh menggunakan aplikasi Publish or Perish. Total peserta dalam studi ini berjumlah 1.200, terdiri atas 370 siswa SD, 208 siswa SMP, 179 siswa SMA, dan 417 mahasiswa. Hasil kajian menunjukkan bahwa model Flipped Classroom berbasis digital dapat meningkatkan kemampuan komunikasi matematis, berpikir kritis, pemahaman konsep, pemecahan masalah, dan berpikir tingkat tinggi. Selain itu, model ini berpengaruh positif terhadap kepercayaan diri siswa, suasana kelas yang lebih interaktif, respons yang baik terhadap pembelajaran, serta mendukung sosialisasi di lingkungan daring. Temuan ini menunjukkan bahwa Flipped Classroom merupakan model pembelajaran yang efektif dan dapat direkomendasikan untuk pembelajaran matematika setelah pandemi.